The worldwide occurrence of Sceliphron caementarium (Drury, 1773) outside its native range, with new records (Hymenoptera: Sphecidae) - Ceccolini, Filippo (Zootaxa, 2023)
Sceliphron caementarium (Drury, 1773) is a Nearctic mud-dauber wasp, accidentally introduced in various parts of the world. All literature records of its distribution outside its native range are summarized and many new records are provided, showing the quick spreading of this species. The countries and the islands in which Sceliphron caementarium occurs are summarized and ordered chronologically according to the date of the first record. The occurrence of the species is first recorded for Argentina, Oman, mainland Spain, the small country of San Marino and the archipelagos of Azores, Canary Islands, and Cayman Islands. Moreover, overall 56 new regions in several countries and 14 new islands are added to those from which the species was previously known. In Russia, the first record of the species is backdated to 2019.